Knowledge, attitude, and practice of lead aprons among dental practitioners and specialists - P Anushya; Maha Lakshmi Jayaraman (Wolters Kluwer Medknow Publications, 2022)
In dentistry, radiographs are often used to diagnose and assess problems relating to oral conditions as well as for better treatment planning. Even though the radiation risk offered by X-rays is minimal, the absorption of this lower level radiation in the individual for a long time challenges a health concern. The aim of the study was to assess the knowledge, attitude and practice of lead aprons among dental practitioners and specialists in Tamil Nadu. A cross-sectional survey was performed around 100 dentists in Tamil Nadu, India, by framing standard questionnaires and collecting responses by online survey forms such as "Google Forms." The statistical study was undertaken with SPSS version 22 and the Chi-square test was selected to determine the correlation. This study showed that lead aprons were regularly used by 63% of participants during radiation exposure. Thirty percent of participants were aware of radiation protection protocol but neglected to use lead aprons routinely (P = 0.113). About 91% of participants gave more preference for thyroid gland to protect it from dental radiation rather than other head-and-neck organs and 82% of them were using thyroid collars for patients during exposure (P = 0.671). Our survey shows that the usage of lead aprons is practiced strictly by dental practitioners under <5 years of clinical experience. However, dental practitioners and specialists were aware of radiation protective aprons but often neglected to use them in practice.